Some Approaches to the Prediction of Permeability Parameters in a Finite Element Program for Early Warning - Krairoj Mahannopkul; Chollada Kanjanakul (Salehan Institute of Higher Education, 2022)
Recently, landslides often occurred in natural soil slopes in the tropical region, which correlate with the rainy season. Rainfall infiltration leads to groundwater level fluctuations. The increased positive pore-water pressures due to rainfall influence have affected the properties and behavior of the unsaturated soil slope. In this research, the Finite Element Method of SEEP/W and SLOPE/W analyzes the factor safety of the slope affected by pore water pressure change due to rainfall. The Soil Water Characteristic Curve (SWCC) and Hydraulic Conductivity function were obtained from sieve analysis and Atterberg's limit. In addition, unsaturated soil properties from the UNSODA code are estimated based on grain-size distribution using the SWRC program. The study area is in Khanom District, southern Thailand. The results show that the soil slope at the site became unstable on November 18, 2021, with F.S. = 1.0, which agrees well with the date of the disaster. In conclusion, the slope stability analysis without the parameters from the unsaturated soil hydraulic database (UNSODA) leads to the F.S. value being higher than the actual value, and the alarm estimation would be inaccurate. Doi: 10.28991/CEJ-2022-08-12-014 Full Text: PDF